Localization of O₂‑sensing ADO‑RGS pathway components in mouse and human kidneys under normoxia, hypoxia and renal fibrosis - Firmke, B. K.M.; Forst, A. L.; Daniel, Christoph; Schley, Gunnar; Broeker, K. A.E. (Pflügers Archiv: European Journal of Physiology, 2026)
Cellular adaptation to hypoxia is essential for maintaining function and survival. While most hypoxic responss are mediated by hypoxia‑inducible factor signaling, the oxygen‑dependent ADO–RGS (2‑Aminoethanethiol-Dioxygenase—Regulator of G‑Protein Signaling) pathway has recently been implicated in oxygen‑sensitive regulation of G‑protein signaling. The kidneys are particularly vulnerable to hypoxia, a major contributor to chronic kidney disease. Because a systematic characterization of ADO and its RGS substrates across renal cell types is lacking, this study examined their spatial expression patterns in mouse and human kidneys under (patho)physiological conditions. Ado and Rgs4, Rgs5, and Rgs16 expression was mapped in mouse kidney sections under normoxic, hypoxic, and fibrotic conditions using RNAscope™, complemented by RT‑qPCR. Mouse data were compared with ADO-RGS expression patterns in human biopsies. Ado expression was uniform across renal regions, cell types, and conditions. Besides its baseline presence in vascular cells, Rgs4 showed strong induction in cortical and outer medullary fibroblasts during anemia. It was also upregulated in fibroblasts and proximal tubules within fibrotic lesions. Rgs5 was highly expressed in vascular structures and demonstrated hypoxia‑induced upregulation in medullary fibroblasts and vasa recta, with moderate induction under fibrotic conditions. Tubular epithelial expression also occurred during fibrosis. Rgs16 was mostly expressed in Pdgfrb⁺ interstitial cells in fibrotic kidneys. Human kidney-disease biopsies also displayed distinct RGS4 and RGS5 expression patterns. Overall, these findings suggest that while ADO is consistently present, the functional impact of ADO–RGS signaling may be driven by dynamic, cell‑type‑specific regulation of RGS genes during acute and chronic hypoxic stress.
CRIS-Team Scopus Importer:2026-07-03
Keywords: ADO-RGS-signaling pathway; Chronic kidney disease; Fibrosis; Hypoxia; O; Spatial transcription